Analisis Faktor-Faktor Yang Mempengaruhi Realisasi Penerimaan Pajak Di Kantor Pelayanan Pajak Pratama Medan Barat - Desi Triana Munthe (Jurnal Riset AKuntansi dan Bisnis, 2021)
This research aims to find out and analyze the effect of tax amnesty on the realization of tax revenues in KPP Pratama Medan Barat. To find out and analyze the influence of tax socialization on the realization of tax revenues in KPP Pratama Medan Barat. To find out and analyze the influence of tax amnesty and tax socialization on the realization of tax revenues in KPP Pratama Medan Barat. The analytical technique used in this study is quantitative data analysis, which is testing and analyzing data with calculations of numbers and then drawing conclusions from the test with track analysis techniques but in practice the processing of data research is not processed manually, but uses SPSS statistical software. From the results of this study, tax amnesty variables have a significant effect on the realization of tax revenues. From the results of this study, tax socialization variables have a significant effect on the realization of tax revenues. From the results of this study, tax amnesty variables and tax socialization have a significant effect on the realization of tax revenues.